Poetry Writing Skills Assisted by Natural Media in Class V Elementary School - Perdana, Rifandi; Cahyani, Isah (International Conference on Elementary Education, 2022)
This study aims to describe the skills of writing poetry with the help of natural media in the fifth grade of SD Negeri 1 Lambheu. In practice, this study uses descriptive qualitative methods with data analysis methods according to Miles and Hubberman which has three steps, namely data reduction, data presentation and conclusion drawing. Data collection techniques in this study using observation, interviews and tests. By paying attention to the findings and discussion, this research has been able to prove that the skills of fifth grade students of SD Negeri 1 Lambheu in writing poetry with the help of natural media already have good skills. The good poetry writing skills assisted by the surrounding natural media is shown through aspects in the assessment of poetry writing skills, Among them are (1) the suitability of the theme and content, (2) the accuracy of diction, (3) the utilization of figurative language, and (4) imagining. The theoretical analysis in the discussion provides broad and in-depth information about the skills of students in writing poetry with the help of the surrounding media so that it will make it easier for students to explore ideas and ideas by observing the surrounding environment.